Optimization of alkali-thermostable and cellulase-free eylanase production from Bacillus Sp. - Sharma, SCD; Shovon, MS; Asaduzzaman, AKM; Jahan, MG Sarowar; Yeasmin, T; Roy, N (Journal of Bio-Science, 2012)
Context: To analyze the nutritional and physicochemical parameters for the production of alkali-thermostable and cellulase free xylanase from bacteria. Objectives: The aim of this study was to isolation and identification and of alkali-thermostable and cellulase free xylanase producing bacteria from soil as well as optimization of process parameters for xylanase production. Materials and Methods: The bacterium Bacillus sp. was isolated from soil by serial dilution technique on xylan agar medium and identified by morphological and biochemical studies. The production of xylanase was carried out on xylan broth medium and xylanase activity was assayed by dinitrosalicylic acid (DNS) method. The effect of cultural parameters on the production of xylanase was determined by measuring the activity of xylanase. The effect of temperature and pH on the activity of partially purified xylanase as well as substrate specificity of xylanase were examined. Results: The maximum xylanase production (4000 U/L) by a Bacillus sp. was attained when the medium containing 0.5% wheat bran xylan and peptone at pH 8.0 and 50-55°C within 48-60 h. The partially purified xylanase was optimally active at pH 9.0 and 55°C. The xylanase showed high substrate activity towards wheat bran xylan but no activity towards cellulose, carboxymethyl cellulose and starch. Thus the enzyme was alkali-thermostable and cellulase free xylanase. Conclusion: The results obtained in this study suggest that the Bacillus sp. used is highly potential and useful for the production of cellulase free xylanase. DOI: http://dx.doi.org/10.3329/jbs.v19i0.12994 J. bio-sci. 19: 7-14, 2011